Response of in vitro obtained oil palm and interspecific OxG hybrids to inoculation with Phytophthora palmivora. Issue 2 (4th February 2019) - Ávila‐Méndez, Kelly; Avila‐Diazgranados, Rodrigo; Pardo, Alonso; Herrera, Mariana; Sarria, Greicy; Romero, Hernan Mauricio
Abstract: Bud rot (BR) disease caused by Phytophthora palmivora is the most devastating disease in oil palm cultivation in America. Oil palms that survived BR epidemics were found in areas highly devastated by the disease; these palms were introduced into Cenipalma's in vitro micropropagation (cloning programme). A severity scale was developed for in vitro palms from five ortets inoculated with two different P. palmivora isolates. Then, eight ortets of Elaeis guineensis and two ortets of the OxG interspecific hybrid were evaluated in two inoculation trials under chamber growth conditions. The clone performance response was consistent with that reported in the field for the corresponding ortets, and two contrasting ortets, one susceptible (ortet 57) and one resistant (ortet 34) were identified. We monitored and compared defence responses to P. palmivora in the contrasting ortets. An increase in reactive oxygen species (ROS) production after inoculation with the pathogen was observed, with higher accumulation of H2 O2 in the resistant plants. Catalase (CAT) activity in resistant plants increased after inoculation with the pathogen from 24 hr post‐infection (hpi) and remained high during the observation time. In the susceptible ortets, there was a significant increase on catalase activity only at 48 hpi. Peroxidase (POS) activity increased in clones from both susceptible and resistant ortets, but the increase was much greater in the susceptible ones. Phenylalanine ammonia lyase activity increased in response to inoculation, and these increases were greater in clones of the susceptible ortet than in clones of the resistant ortet.